Evaluation of the potential of a simplified co-delivery system with oligodeoxynucleotides as a drug carrier for enhanced antitumor effect - Liu CX (Dove Medical Press, 2018)
Chunxi Liu,1,* Tingxian Liu,2,* Yongjun Liu,2 Na Zhang2 1Department of Pharmacy, Qilu Hospital, Shandong University, Ji’nan, China; 2School of Pharmaceutical Science, Shandong University, Ji’nan, China *These authors contributed equally to this work Background: We previously developed a simple effective system based on oligodeoxynucleotides with CGA repeating units (CGA-ODNs) for Dox and siRNA intracellular co-delivery. Methods: In the present study, the in vitro cytotoxicity, gene transfection and in vivo safety of the co-delivery system were further characterized and discussed. Results: Compared with poly(ethyleneimine) (PEI), both CGA-ODNs and the pH-sensitive targeted coating, o-carboxymethyl-chitosan (CMCS)-poly(ethylene glycol) (PEG)-aspargine-glycine-arginine (NGR) (CMCS-PEG-NGR, CPN) showed no obvious cytotoxicity in 72 h. The excellent transfection capability of CPN coated Dox and siRNA co-loaded nanoparticles (CPN-PDR) was confirmed by real-time PCR and Western blot analysis. It was calculated that there was no significant difference in silencing efficiency among Lipo/siRNA, CPN-modified siRNA-loaded nanoparticles (CPN-PR) and CPN-PDR. Furthermore, CPN-PDR was observed to be significantly much more toxic than Dox- and CPN-modified Dox-loaded nanoparticles (CPN-PD), implying their higher antitumor potential. Both hemolysis tests and histological assessment implied that CPN-PDR was safe for intravenous injection with nontoxicity and good biocompatibility in vitro and in vivo. Conclusion: The results indicated that CPN-PDR could be a potentially promising co-delivery carrier for enhanced antitumor therapy. Keywords: co-delivery, doxorubicin, VEGF, cytotoxicity, transfection